Perbandingan Efektivitas dalam Sistem Pembayaran Sistem Kliring Nasional Bank Indonesia (SKNBI) dengan Bank Indonesia Real Time Gross Settelment (BI-RTGS) pada PT Bank SUMUT KCP Syariah Simpang Kayu Besar - Nur Salsabila Arwan Nasution; Nurul Inayah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research is entitled "Comparison of Effectiveness in the Payment System of the National Clearing System of Bank Indonesia (SKNBI) and Bank Indonesia Real Time Gross Settlement (BI-RTGS) at the Bank of the Sumatran sharia bank Simpang Kayu Besar ". The purpose of this paper is to compare the mechanism of the Bank Indonesia National Clearing System (SKNBI) with Bank Indonesia Real Time Gross Settlement (BI-RTGS) to see the effectiveness of the smooth payment system at the Simpang Kayu Besar Syariah Bank. The type of data used in this paper is primary data obtained through observation and interviews with the bank, namely employees of the bank teller of the Sumatran sharia bank Simpang Kayu Besar, and secondary data obtained by approaching or documenting archives, documents, and records. The data analysis method used in this paper is a qualitative descriptive analysis method. The conclusions that can be drawn from this report are (1) The implementation of these two payment systems has been carried out properly and in accordance with the stipulated provisions or regulations of Bank Indonesia; (2) The payment system through the BI-RTGS mechanism is more effectively used for the smooth running of the payment system at Bank Indonesia Jambi than through the SKNBI mechanism in terms of the implementation mechanism and in terms of the time required for the settlement process because the settlement process is faster, but from in terms of the cost of the payment system through the SKNBI mechanism is more effective than through the BI-RTGS mechanism because the costs are relatively cheap, so that the payment system through this mechanism is more in demand by the public, and; (3) On the integration side, the Bank Indonesia National Clearing System is more effective even though it is carried out at certain times, either by Bank Indonesia itself, banks or through seminars held by universities in Jambi. Meanwhile, BI-RTGS is not yet effective and socialization has not been maximized, either directly or indirectly. So many people do not know the advantages and disadvantages of this payment system.